A nanostructured chromium(iii) oxide/tungsten(vi) oxide p–n junction photoanode toward enhanced efficiency for water oxidation1. Issue 26 (14th July 2015) - Hu, Zhuofeng; Xu, Mingkun; Shen, Zhurui; Yu, Jimmy C.
<x xml:space="preserve">Abstract</x> A nanostructured Cr2O3/WO3 p–n junction photoanode has been prepared for achieving high efficiency in water oxidation.